Less is More: Low-dose Prothrombin Complex Concentrate Effective in Acute Care Surgery Patients. Issue 6 (June 2015) - Quick, Jacob A.; Meyer, Jennifer M.; Coughenour, Jeffrey P.; Barnes, Stephen L.
Optimal dosing of prothrombin complex concentrate (PCC) has yet to be defined and varies widely due to concerns of efficacy and thrombosis. We hypothesized a dose of 15 IU/kg actual body weight of a three-factor PCC would effectively correct coagulopathy in acute care surgery patients. Retrospective review of 41 acute care surgery patients who received 15 IU/kg (610%) actual body weight PCC for correction of coagulopathy. Demographics, laboratory results, PCC dose, blood and plasma transfusions, and thrombotic complications were analyzed. We performed subset analyses of trauma patients and those taking warfarin. Mean age was 69 years (18–94 years). Thirty (73%) trauma patients, 8 (20%) emergency surgery patients, 2 (5%) burns, and 1 (2%) non-trauma neurosurgical patient were included. Mean PCC dose was 1305.4 IU (14.2 IU/kg actual body weight). Mean change in INR was 2.52 to 1.42 (p 0.00004). Successful correction (INR <1.5) was seen in 78 per cent. Treatment failures had a higher initial INR (4.3 vs 2.03, p 0.01). Mean plasma transfusion was 1.46 units. Mean blood transfusion was 1.61 units. Patients taking pre-hospital warfarin (n = 29, 71%) had higher initial INR (2.78 vs 1.92, p 0.05) and received more units of plasma (1.93 vs 0.33, p 0.01) than those not taking warfarin. No statistical differences were seen between trauma and nontrauma patients. One thrombotic event occurred. Administration of low-dose PCC, 15 IU/kg actual body weight, effectively corrects coagulopathy in acute care surgery patients regardless of warfarin use, diagnosis or plasma transfusion.